Antioxidant protection of cooked meatballs during frozen storage by whey protein edible films with phytochemicals from Laurus nobilis L. and Salvia officinalis. (April 2017) - Akcan, Tolga; Estévez, Mario; Serdaroğlu, Meltem
Abstract: The aim of this study was to assess the effectiveness of whey protein isolate based edible films (WPFs) incorporated with natural antioxidant extracts (NAE) from laurel (LA, Laurus nobilis L.) or sage (SA, Salvia officinalis.) on the oxidative stability of cooked meatballs during frozen storage at −18 °C for 60 days. TBA values of the meatballs with NAE-WPF were lower than the TBA values of the meatballs with WPF and the control (C) group of samples. Higher antioxidant activity by LA-WPF than SA-WPF was determined with a 2, 2′-diphenyl-2-picrylhydrazyl radical-scavenging assay. Incorporation of NAE from LA or SA into the edible films (EFs) resulted in reduced para -Anisidine value (p-Av) (P < 0.05) in cooked meatballs. Total phenolic compound content was higher in meatballs treated with NAE-WPF than in the C group suggesting that these natural compounds contributed to the oxidative stability of frozen meatballs. This study shows that the application of an antioxidant active packaging with LA or SA to meatballs is a feasible and effective antioxidant strategy for retarding oxidative changes in cooked and subsequently frozen comminuted meat products. Highlights: Ready-to-eat meatballs are more vulnerable to oxidation during frozen storage. Edible film applications are important in the way of sustainability in food industry. Phytochemicals from Laurus nobilis L . and Salvia officinalis have effect against oxidation. Antioxidant protection of ready-to-eat meatballs is required to preserve quality.